(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article analyzes the integration of innovative technologies into the taxation processes of legal entities. It discusses the main directions of digital transformation, the advantages and challenges of implementing modern technologies such as artificial intelligence, Big Data, blockchain, and digital platforms. Special attention is paid to the impact of digitalization on transparency, efficiency, and risk mitigation in tax administration, as well as the requirements for the adaptation of legal, technical, and organizational frameworks. The article also highlights the future prospects and strategic importance of technological modernization in corporate taxation.